A rare cause of acquired methemoglobinemia - vurimi, Jahnavi; Sarkar, Anirban; abdullah , N fahim; Jayanth, Komal Krishna (Indian Journal of Case Reports, 2026)
Methemoglobinemia is a life-threatening clinical condition with a favorable outcome when diagnosed and treated promptly. It should be suspected in patients with oxygen saturation of around 85% that does not improve despite supplemental oxygen therapy. We report the case of a 48-year-old male with acquired methemoglobinemia due to the consumption of complementary alternative medicine (Ayurvedic medication for chronic kidney disease), who had a good outcome on treatment with Methylene blue. In refractory cases not responding to methylene blue, exchange transfusion is an effective alternative treatment.